HUBUNGAN USIA, TINGKAT PENGETAHUAN DAN KEPATUHAN MINUM FE TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL - Eva Yani; Sulhawa; Titin Dewi Sartika; Erma Puspita Sari (LPPM STIKes Mitra Adiguna, 2023)
The World Health Organization (WHO) states that anemia is the 10 biggest health problem in this modern century, where groups at high risk of anemia are women of childbearing age, pregnant women, school-age children, and adolescents. The design of this research is an analytic survey with a cross sectional design. The population in this study were all pregnant women who came and checked their contents at the Sidorahayu Health Center, Musi Banyuasin Regency until July 2021, totaling 231 respondents. The results of univariate analysis, from 70 respondents found that 48 people (68.6%), 44 people (62.9%) were in the high risk age category, 42 people (60%), had less knowledge, 52 people (74.3 %) did not comply with consuming Fe. Based on the results of the chi-square test, the Asymp Sig value (2 sides) = 0.000 or p value < (0.05), which means that there is a relationship between age and the incidence of anemia, then for knowledge, the Asymp Sig value (2 sides) = 0.002 <0.05 which means there is a relationship between consumption compliance with the incidence of anemia, then for knowledge, the Asymp Sig value (2 sides) = 0.000 <0.05